Mengenal Sistem Operasional, Jasa dan Produk Perbankan Syariah - Wahyudin Maguni (Institut Agama Islam Negeri (IAIN) Kendari, 2008)
The concept of Islamic banking (hereinafter referred to as Syariah banking) 1) is new to the people of Indonesia, including to the Muslim community itself, although the basic concept of sharia banking has been running for a long time, in reality in Indonesia the practice of sharia banks is new started in 1992. Based on the fact that the practice of sharia banking is new in the early stages (On infant state), it is reasonable if it is still poorly understood by the community, so some of them looked with a hope of anxiety and doubt at the same time.One of the obstacles faced is the slow process of socializing the Syariah banking system. This is not only due to the limited network of Syariah banking services, but also because of the lack of Islamic banking studies centers in particular and Islamic economics in general. Understanding of Syariah banking system is not enough only done through technical socialization. Background and history of the development of the thought of the scholars and Muslim scholars until the realization of the concept of sharia banking system also needs to be socialized.We should be grateful that currently Law No. 10/1998 on the Amendment of Act Number 7 of 1992 concerning banking has broadly accommodated the implementation of Syariah banking in the midst of the banking system that has been running for this. In other words, under the Act, our banking system has adopted a dual banking system.This paper is intended to participate briefly in its birth, its operational system, its position in Indonesian banking law, and the need for the socialization of Syariah banking.